1997
DOI: 10.1023/a:1012109329631
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Confocal laser scanning microscopy is a suitable approach to visualize the transport pathways of high molecular weight hydrophilic compounds across nasal epithelium, and to study the effects of absorption enhancers on drug transport and cell morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Cyclodextrins may affect nasal mucosal membranes in the same manner, thus allowing their extended use as adjuvants to improve the nasal absorption of poorly absorbable peptide and protein drugs. The lipid solubilization mediated by cyclodextrins may cause changes in transcellular processes, and these changes are believed to be transmitted to the paracellular region, which appears to be the most likely route for the transport of polypeptides. , …”
Section: Hydrophilic Cyclodextrins As Absorption Enhancersmentioning
confidence: 99%
“…Cyclodextrins may affect nasal mucosal membranes in the same manner, thus allowing their extended use as adjuvants to improve the nasal absorption of poorly absorbable peptide and protein drugs. The lipid solubilization mediated by cyclodextrins may cause changes in transcellular processes, and these changes are believed to be transmitted to the paracellular region, which appears to be the most likely route for the transport of polypeptides. , …”
Section: Hydrophilic Cyclodextrins As Absorption Enhancersmentioning
confidence: 99%
“…Recently, it has been shown that intranasal MMP-9 can be used as a local nasal permeability enhancer [ 116 ]. It is important to keep in mind that nasal permeability enhancers cause significant nasal irritation and mucosal toxicity [ 117 ], and additional studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The concomitant intranasal administration of ( 125 I)I-IgG and MMP-9 significantly improved the uptake of antibody into the brain as compared to unformulated antibody ( Kumar et al, 2018 ). However, permeability enhancers should be used with caution as mucosal irritation and toxicity has been reported ( Maher et al, 2016 ; Marttin et al, 1997 ). Another method consists in improving transcellular transport using cell-penetrating peptides: short-length (5–30 amino-acids) peptides, rich in positive charges and containing hydrophobic tryptophan residues may help translocation across epithelium.…”
Section: Fcrn and Cellular Barriersmentioning
confidence: 99%